Building domain specific languages upon the dbject constraint language (DCl) - Domínguez Iglesias, Antonio (1999)
The paper aim is to demonstrate how to extend oel, both with new data struetures and operations, in order to use it as a domain specific specification language. This data structures and operations are domain specific, and identified as a result of a domain analysis process. In conjunction with appropriate transformation techniques it will be possible togenerate code directly from system specifications.